2021
DOI: 10.3389/fmicb.2021.683481
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriomic Analyses of Asian Citrus Psyllid and Citrus Samples Infected With “Candidatus Liberibacter asiaticus” in Southern California and Huanglongbing Management Implications

Abstract: Citrus Huanglongbing (HLB; yellow shoot disease) is associated with an unculturable α-proteobacterium “Candidatus Liberibacter asiaticus” (CLas). HLB was found in southern California in 2012, and the current management strategy is based on suppression of the Asian citrus psyllid (Diaphorina citri) that transmits CLas and removal of confirmed CLas-positive trees. Little is known about Asian citrus psyllid-associated bacteria and citrus-associated bacteria in the HLB system. Such information is important in HLB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…A metagenomic pipeline was developed for bacteriomic analysis of HLB and ACP using next-generation sequencing techniques ( Huang et al, 2021 ). The study identified bacteria in both, citrus as a host plant and vector psyllids, which included Buchnera , Bradyrhizobium , Burkholderia , “ Candidatus Carsonellaruddii,” “ Candidatus Profftella armature,” C Las, Pseudomonas, Mesorhizobium , Paraburkholderia , and Wolbachia .…”
Section: Citrus Microbiome and Incurring Huanglongbing: A Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A metagenomic pipeline was developed for bacteriomic analysis of HLB and ACP using next-generation sequencing techniques ( Huang et al, 2021 ). The study identified bacteria in both, citrus as a host plant and vector psyllids, which included Buchnera , Bradyrhizobium , Burkholderia , “ Candidatus Carsonellaruddii,” “ Candidatus Profftella armature,” C Las, Pseudomonas, Mesorhizobium , Paraburkholderia , and Wolbachia .…”
Section: Citrus Microbiome and Incurring Huanglongbing: A Case Studymentioning
confidence: 99%
“…The study identified bacteria in both, citrus as a host plant and vector psyllids, which included Buchnera , Bradyrhizobium , Burkholderia , “ Candidatus Carsonellaruddii,” “ Candidatus Profftella armature,” C Las, Pseudomonas, Mesorhizobium , Paraburkholderia , and Wolbachia . Such an outcome would be highly useful in understanding HLB biology and its management ( Huang et al, 2021 ). Profiling of endophytic microbes in HLB-infected and HLB-free leaf midribs of Shatangju mandarin, employing next generation sequencing, revealed 53 endophytic bacterial orders through 12 phyla and 24 endophytic fungal orders distributed through 2 phyla in healthy leaf midribs ( Yan et al, 2021 ).…”
Section: Citrus Microbiome and Incurring Huanglongbing: A Case Studymentioning
confidence: 99%
“…Of particular interest was sample #9 from Hidalgo with a Ct of 36.99 by CLas4G-PCR. Such a high Ct value could have been attributed to the presence of non-CLas bacteria ( Huang et al., 2021 ). However, when sample #9 was cross-checked using the more sensitive RNRf-PCR, a lower Ct value confirmed the presence of CLas ( Bao et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 in Table 1 ) and BCSMX (Term-A) from Baja California Sur (No. 37 in Table 1 ) were selected for whole genome sequencing following the procedure described previously ( Zheng et al., 2014 ; Huang et al., 2021 ). Briefly, 2–4 µl of sample DNA (mixture of bacteria + ACP) was enlarged (i.e., increased all DNA simultaneously) with GenomiPhiTM V2 DNA Amplification kit (GE Healthcare, Sigma-Aldrich Corp., St. Louis, MO, USA) following manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Despite having significant impacts on the citrus industry worldwide, there are limited 16S rRNA gene sequence surveys available on D. citri populations [1,2]. Outside of two core bacterial endosymbionts Candidatus Carsonella ruddii and Candidatus Profftella armatura, and in addition to the facultative bacterial endosymbiont Wolbachia wDi, no other symbionts are well characterized [1][2][3][4][5][6][7]. Like other hemipteran and sap-sucking insects, D. citri relies on nutritional supplementation delivered by one of its core endosymbionts, Ca.…”
Section: Introductionmentioning
confidence: 99%